Impact of the Trophic Effects of the Secretome From a Multistrain Probiotic Preparation on the Intestinal Epithelia. Issue 6 (10th December 2020) - Petito, Valentina; Greco, Viviana; Laterza, Lucrezia; Graziani, Cristina; Fanali, Caterina; Lucchetti, Donatella; Barbaro, Maria Raffaella; Bugli, Francesca; Pieroni, Luisa; Lopetuso, Loris Riccardo; Sgambato, Alessandro; Sanguinetti, Maurizio; et al.
Abstract: Background: Probiotics are defined as live, nonpathogenic bacteria that confer health benefits beyond their nutritional value. In particular, VSL#3 exhibits demonstrated efficacy in the management of diseases characterized by an increased intestinal permeability. Our study aimed to understand how VSL#3 promotes gut health by secreting bioactive factors and identify which human pathways are modulated by secretome derived from the VSL#3 formula. Methods: Two different lots of VSL#3 were used, and Caco-2 cell line was treated with conditioned media (CM) prepared using 1 g of the probiotic formula. We evaluated the effects of the probiotics on cellular proliferation and apoptosis by cytometry and the expression of tight junction proteins by western blotting. A proteomics analysis of both culture media and the whole proteome of Caco-2 cells treated with VSL#3-CM was performed by nano-ultra performance liquid chromatography - tandem mass (nUPLC MS/MS) spectrometry. Results: The probiotic formula increased cell proliferation, decreased cellular apoptosis cells, and increased re-epithelialization in the scratch assay. Several peptides specifically synthetized by all the species within the probiotic preparation were recognized in the proteomics analysis. Human proteins synthesized by CaCo-2 cells were also identified. Conclusions: To our knowledge, this manuscript describes the first evaluation of the probiotic secretome, and the results showed that the improvement in intestinal barrier functions induced by probiotics seems to be accompanied by the modulation of some human cellular pathways.